Tight - Maldonado, Torrey (New York, NY : Nancy Paulsen Books, 2018)
After his quick-tempered father gets in a fight and is sent back to jail, sixth-grader Bryan, known for being quiet and thoughtful, snaps and follows new friend Mike into trouble.
Keywords: Conduct of life -- Juvenile fiction; Inner cities -- Juvenile fiction; Families -- Juvenile fiction -- Brooklyn (New York, N.Y.); Friendship -- Juvenile fiction; African Americans -- Juvenile fiction; Conduct of life -- Fiction; Inner cities -- Fiction; Family life -- Fiction -- Brooklyn (New York, N.Y.); Friendship -- Fiction; African Americans -- Fiction; JUVENILE FICTION / Boys & Men; JUVENILE FICTION / People & Places / United States / African American; JUVENILE FICTION / Social Issues / Friendship; Brooklyn (New York, N.Y.) -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Fiction